Evaluation of electronic trading processes as a tool for public hospital pharmaceutical assistance management - ÉRICA CRISTINA DOURADO SILVA; FÁBIO JORGE RAMALHO DE AMORIM; EDÉLZIO ALVES COSTA JÚNIOR; IZADORA MENEZES DA CUNHA BARROS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
Background: The trading system is one of the main modalities of the bidding process for the acquisition of medicines, mainly through rationalization, agility, transparency of the process and economy. Objective: To evaluate the influence of the electronic trading processes in the management of public hospital pharmaceutical services. Methods: This is an observational, transversal and retrospective study, in which the bidding processes for 2015 of a teaching hospital in the state of Sergipe were analyzed. The internal processes and technical opinions, as well as the minutes of the electronic trading sessions available at www.comprasgovernamental.gov.br, were used as sources of information and data collection. Results: Eight bidding processes were analyzed, with a total of 199 items tendered, of which 25.6% were unsuccessful and 7% remained deserted. There was an average of 158.87 days to complete the entire bidding process. The main reasons for the failure of the items were the non-compliance with the documentation required in the bidding process (42.4%) and the value of the proposals being above the estimated (17%). As for the XYZ classification of the failed and deserted items, 18.5% were classified as of the highest criticality (Z). Conclusions: The time for completion of the bidding processes was extensive, mainly referring to the internal phase, which ratifies the need to establish deadlines for completion of the steps with the intuition of speeding up the purchase process. Deserted and failed bids may directly influence the patient's clinical outcome due to the shortage of medicines and medical-hospital supplies, and consequently the discontinuity of care provided to the patient.